Mecanismos de regeneração natural em área incendiada em uma Floresta Ombrófila Densa Montana, Espírito Santo, Brasil - Teixeira, Juliana Macedo Gitahy (2017)
Climate change and fragmentation are increasing the frequency and intensity of forest fires in rainforest regions. Evaluating how forest recovers after fires is important to understand compositional, structural and functional changes in the community and to plan restoration. Resprouting ability and prompt germination of pioneers are common mechanisms of forest regeneration after fires. We evaluated the relative importance of resprouting, as a functional trait of species persitence after fire, seed germination, seedling and tree survivors as mechanisms of forest regeneration, comparing burnt and unburnt forests in montane Atlantic rainforest (Serra do Valentim, Iúna, Espírito Santo, Brasil). Survey was done in 30 (5x10m) plots (2 control sites and 1 site burned in 2014), by counting and classifying stems in survivors, regenerating, resprouters (root, base and stem sprout) and soil seed bank. After evaluated community structure, we run ordination analyses (PcoA and LDA) to understand how the species composition are distributed by area and mechanism, and which mechanism has the greatest weight for the natural regeneration in each area. We sellected the species representing 80% of the community dominancy and collected functional traits related to persistense, establishment and dispersion. With a CWM and species × traits matrix we run another PCoA, how the traits are distributed between species and how they can be related with the performance in the areas. We found that resprouting can be a mechanism and a functional trait of fundamental importance for natural regeneration and resilience of communities after fire, ensuring for some species their persistense and survival. However seed bank contribute with pioneers species, essential dor reassembly.